Does Breast Cancer Risk Awareness Motivate Personal Prevention Practices: Findings from a Community-based Assessment? - Ouma, J.; Olang’, S.; Asweto, Collins O.; Obago, I. T.; Kaseje, D. (My University, 2016)
Breast cancer, is the leading cause of cancer specific mortality. But nearly 80% of the mortality is preventable by early diagnosis. We assessed knowledge and practice of breast cancer prevention by women in a rural community setting. Data was collected on demographics, family history, knowledge and practice of breast cancer by interviewer administered questionnaire. Knowledge (including knowledge of risk) and practice were measured using a response-based score to a set of 9 and 10 questions respectively. Prevalence odds ratio was calculated to estimate association between independent and outcome variables. Knowledge of breast cancer risk was low (14.2%). Family history and socioeconomic status were significantly associated with knowledge; respondents with more than eight years of school were more likely to have higher knowledge (OR=2.859; CI=1.578-5.178). Practice of prevention was equally low (17.2%). Practice was significantly associated with knowledge; respondents with higher knowledge of prevention were more likely to practice prevention (OR=6.8; CI=3.308-14.104). We propose that community-based risk communication and awareness creating programs may motivate breast cancer prevention practices. Women of lower socio-economic status should especially be targeted with such interventions. There is need to develop these into a sustainable community-based health education program.
Keywords: breast cancer; knowledge practice; community prevention